Optimalisasi Edukasi Bahaya Napza pada Remaja di Sekolah Menengah Pertama Negeri 2 Kota Sorong - junaiddin, junaiddin; Andirwana, Andirwana; R, Astuti; Etnis, Baktianita Ratna; Taborat, Miranda (PT.Mantaya Idea Batara, 2024)
Adolescence is a period of change for a person both physically and psychologically because there is a transition from childhood to pre-adolescence to adulthood. Drugs or what is usually called narcotics is an abbreviation of narcotics, psychotropic subtances and other additives. Drug abuse among school teenagers reached 2.29 million according to research the total number including drugs in 2019, most of the first drugs users were between the ages of 17 – 19 years, which means they are still in the teenage category. Various efforts can be made to prevent drug abuse among Teenagers, including increasing activities with religious nuances, counseling and socializing the impacts and dangers that can be caused by drug abuse among students, communicating with students parents, and trying to be careful with serious about the problem of drug abuse. This service aims to increase students awareness and views about the dangers of drugs use and how to overcome them. This service was held on Wednesday, March 29 2023 at SMPN 2 Sorong City, Southwest Papua. The budget for this activity is capitalized by the activity implementers. Implementation was carried out in the form of counseling and question and answer discussion. Participants in this activity were students from class VII and VIII with a total of 30 people. This service activity was well organized and received a positive response, so that the expected goals could be achieved as evidenced by the enthusiasm of students asking questions in this activity